Missiological Perspectives from Germany: Innovation and Mission in Rural Areas - Herbst, Michael (Ecclesial Futures, 2020)
This article argues for innovation and mission in the Lutheran Churches of Germany. The authors approach this topic by drawing on research on innovative and missional projects in rural areas in Germany. The authors are looking at rural areas where few people would expect innovation. Presenting a study called “Landwards” and the evaluation of exemplary projects in rural areas in Eastern Germany, it is possible to review key factors for innovative and missional church development. One of the most intriguing factors is that, compared to international studies on missional church development (like fresh expressions of church in the Church of England or pioneering places in the Protestant Church in the Netherlands), it can be shown that lay leaders do not play the dominant role in starting the initiatives. However, lay people organized in teams do seem to be the engine of on-going innovative initiatives in rural areas. This raises different questions regarding the training of leaders, for example, or the collaboration of such initiatives with established churches. The “Landwards” study points out the possibilities of innovation in rural areas in and adjacent to the Lutheran structure of being a “Volkskirche.” This is a rather original way to deal with the challenges of being a state-like church in Germany.